Clinical genetic study in juvenile myoclonic epilepsy - Cvetkovska, Emilija; Panov, Sasho; Kuzmanovski, Igor (My University, 2014)
To evaluate clinical features of probands with juvenile myoclonic epilepsy (JME) and affected members of their families in order to study clinical genetics of JME.